A Universal C-arm Language Improves OR Morale: Original Research - Nielsen, Ena; Bauer, Jennifer M. (Journal of the Pediatric Orthopaedic Society of North America, 2022)
Background: Miscommunication while using intraoperative fluoroscopy C-arm can increase frustration, time, and radiation exposure. There have been no studies to date that have examined a standardized C-arm language during live cases, nor its durability over time. We aimed to design a directive language for use at a single institution and compare pre- and post-implementation surgeon and radiology technologist satisfaction and sense of operative efficiency. Methods: All surgeons regularly using intraoperative fluoroscopy and all radiology technicians were surveyed regarding their experience and satisfaction regarding C-arm usage. Respondents provided their preferred terminology for each C-arm motion; the most frequent responses for each movement were used to create a universal language. Users were educated on the language via email and OR/C-arm signage for 1 month. Participants’ recall of the terminology and satisfaction with the use of the C-arm was evaluated at 1- and 3-months post-intervention. Results: 57 people responded to the initial survey—30 radiology technicians and 27 surgical attendings. Initially, surgeons indicated significantly greater need to correct C-arm movement and repeat fluoroscopy and more case delays due to miscommunication than radiology technicians. At 3 months, surgeons reported significant improvements in how often the C-arm movement had to be corrected due to miscommunication (p=0.007), frustration due to C-arm miscommunication (p=0.002), and frequency of operative delays due to C-arm miscommunication (p=0.03). At 1 month, participants were able to recall the standardized language terms 76.9% of the time (surgical attendings: 74.4%, radiology technicians: 79.2%). This decreased slightly to 72.2% at 3 months (surgical attendings: 66.7%, radiology technicians: 77.6%). Conclusions: Training in a universal C-arm language significantly improved surgeon but not radiology technician experience using C-arm intraoperatively, with decreased frustration and perceived improvements in efficiency. There was good retention of the language terms at 3 months.